Synthesis of chiral supramolecular bisphosphinite palladacycles through hydrogen transfer-promoted self-assembly process. Issue 72 (22nd August 2018) - Vasseur, Alexandre; Membrat, Romain; Palpacelli, Davide; Giorgi, Michel; Nuel, Didier; Giordano, Laurent; Martinez, Alexandre
Abstract : P -Chiral secondary phosphine oxides react with Pd2 (dba)3 in an acidic medium to provide chiral supramolecular bisphosphinite palladacycles through a H-transfer-based self-assembly process prior to SPO-promoted oxidative addition of an acid to a Pd(0) centre. Abstract : P -Chiral secondary phosphine oxides react with Pd2 (dba)3 in an acidic medium to provide chiral supramolecular bisphosphinite palladacycles through a H-transfer-based self-assembly process prior to SPO-promoted oxidative addition of an acid to a Pd(0) centre. The one-pot methodology allows variations of the X-type ligand as desired. Eight complexes have been characterised by X-ray diffraction.